So schaffen wir das - eine Zivilgesellschaft im Aufbruch 90 wegweisende Projekte mit Geflüchteten - Eilert, Anne; Rudloff, Marlene; Schiffauer, Werner (Kultur und soziale Praxis, 2017)
While dealing with the challenge of fleeing from war and poverty, the German civilian society has reinvented itself. Between 2015 and 2016 approximately 15,000 projects were established and creative answers to the manifold challenges of immigration were found. They provide an alternative to panic reactions that consider controls and deterrence to be the only means of how to deal with refugees. This volume describes 90 exemplary projects. They show how much power to master social problems can be found in today's civilian society - and how much potential for a new kind of interacting not only with immigrants but also within the society itself.